2019
DOI: 10.17061/phrp2931922
|View full text |Cite
|
Sign up to set email alerts
|

Talking about a nanny nation: investigating the rhetoric framing public health debates in Australian news media

Abstract: Objectives and importance of study: News media portrayal of public health issues influences public opinion, policy action and decision making. This study aimed to analyse the use of 'nanny state' frames in Australian news media coverage; identify the stakeholders invoking this frame; determine which public health-related policies attract such framing; and investigate whether 'nanny state' framing is directly challenged in news coverage. Study type: A qualitative framing analysis.Methods: Articles featuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…There was little challenge to this hyperbole from nutrition advocates, which is consistent with findings from other studies which found health advocates did little to contest nanny-state rhetoric when used by opponents of regulation. 45,46 Two sectors were predominantly utilised as expert sources by the Australian news media, nutrition advocates and the food industry. While nutrition advocates dominated newspaper commentary, the messages between public health organisations and individual nutrition spokespeople were not always consistent which contrasted with the united messages from food industry.…”
Section: Discussionmentioning
confidence: 99%
“…There was little challenge to this hyperbole from nutrition advocates, which is consistent with findings from other studies which found health advocates did little to contest nanny-state rhetoric when used by opponents of regulation. 45,46 Two sectors were predominantly utilised as expert sources by the Australian news media, nutrition advocates and the food industry. While nutrition advocates dominated newspaper commentary, the messages between public health organisations and individual nutrition spokespeople were not always consistent which contrasted with the united messages from food industry.…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicate that the alcohol industry is effective at driving certain views or arguments in the media to influence public policy. Common arguments opposing preventive policies can include 'nanny state' frames [55], rejection of government regulation [54] and marginalisation of public health evidence [53]. Studies looking at public commentary of other contested prevention policies have found that stakeholders' views on the UK's soft drinks industry levy differed based on their position or vested interests [56,57].…”
Section: Introductionmentioning
confidence: 99%
“…Although some research has examined how arguments supporting or opposing tobacco control policies have been framed, these studies have mainly been conducted in high-income countries with progressive tobacco control policies. [4][5][6][7] In Africa, where demand for cigarettes is projected to keep increasing, 8 9 and where implementation of tobacco control measures is relatively limited, 10 few studies have explored how tobacco control has been represented in the news media. 11 12 In May 2018, public consultations were opened on South Africa's (SA) proposed Control of Tobacco Products and Electronic Delivery Systems Bill (hereafter 'the Bill').…”
Section: Introductionmentioning
confidence: 99%